Historical context of social, environmental and corporate governance (ESG) and its impacts on organizations: A literature review - Nascimento, Leonardo Dias; Acruz, Carla Santos; Silva , Joelma Veras da; Silva, José Antonio da; João, Belmiro do Nascimento; Pacheco, Clecia Simone Gonçalves Rosa; Santos, Reinaldo Pacheco dos; Nascimento , Deise Mara do; Silva, Ívina Mariana Duarte Marinho e; Silvestre, Guilherme Zullo; Benvindo, Janaina dos Santos (Seven Editora, 2024)
The objective of this research was to explore the historical development of social, environmental and corporate governance and its impacts on organizations. To this end, a bibliographic research was carried out through the survey of articles on the SciELO, Google Scholar and Scopus platforms. As a result, it was found that social, environmental, and corporate governance (ESG) has emerged as a crucial paradigm in contemporary business management, reflecting a transformation in societal expectations about the role of organizations. This literature review addressed the historical development of ESG governance and its impacts, from the emergence of the corporate social responsibility movement to its expansion to include environmental and governance issues. It was evidenced that ESG governance profoundly influences financial performance, brand reputation, risk management, and stakeholder engagement in organizations, promoting greater resilience, attracting investors and conscious consumers. It is crucial for organizations to recognize the importance of ESG governance and incorporate it into their operations and strategies, benefiting not only themselves but also contributing to the sustainable development of society. Despite the benefits, challenges such as the lack of standardization in the disclosure of information and the need for robust metrics still persist, requiring collaborative efforts between companies, investors, regulators, and other stakeholders. In summary, ESG governance is essential for long-term value creation, enabling companies to contribute to a more just, equitable, and sustainable world by embracing its principles. DOI:https://doi.org/10.56238/sevened2024.010-007